(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes the ethnic history and composition of the population of industrial cities of the Tashkent region on the basis of field research, scientific literature and archival documents. Using the example of ethnotonyms existing in the region, it is illustrated that the local part of the oasis population mostly belongs to the representatives of the Turkic language group and is partially Tajik-speaking. Scientific data revealed that the formation of settlements in the region, whose inhabitants were native speakers of European languages, date back to the beginning of the twentieth century, and the migration of the main population is directly related to the emergence of industrial enterprises in the region, the construction of various hydroelectric power plants, as well as the deportation of certain peoples. In addition, survey results confirm that industrial cities have a multi-ethnic environment in which the emergence of mixed cultural traits has led to an increase in the number of families between representatives of different ethnic groups.